Parents’ Motivation for Choosing Bilingual Schools and the Role of English Day Programs in Indonesia - Hanik, Asmah; Nurkamto, Joko; Setyaningsih, Endang (JOLLT Journal of Languages and Language Teaching, 2025)
In this era of globalization, equipping children with English language skills is very important. Bilingual schools have become a popular choice for parents, as they believe English is important because it is an international language. The English Day program plays a crucial role in creating a learning environment that supports structured language use, fostering a comfortable and enjoyable habit of using English. However, the specific reasons for choosing this school and the contribution of English Day to the linguistic and academic development of children still need to be researched further. Therefore, this research attempts to explore the reasons why parents enroll their children in bilingual schools and how the role of English Day in bilingual schools can help them become more proficient in English. This research uses a qualitative approach with a narrative inquiry method. The researcher used semi-structured interviews to collect data and analyzed it using Braun & Clarke’s thematic analysis. From The research findings reveal the main motivations that parents enroll their kids in bilingual schools to make sure they learn English, enjoy a stimulating atmosphere, and become ready for college. Initiatives like English Day improve language proficiency, add enjoyment to the learning process, and encourage critical and creative thinking while offering useful real-world experience. The implications of this research emphasize the importance of delving deeper into parents’ motivations to inform educational policies and practices; this research can assist parents in making more informed decisions regarding school choices for their children. This research contributes to the understanding of bilingual education choices, highlighting the practical value of English.